Association between age at menarche and blood pressure in adulthood: is obesity an important mediator?. Issue 10 (October 2018) - Werneck, André; Oyeyemi, Adewale; Cyrino, Edilson; Ronque, Enio; Szwarcwald, Célia; Coelho-e-Silva, Manuel; Silva, Danilo
Abstract We investigated the association between age at menarche, and adiposity and blood pressure in adulthood, as well as the mediation effects of adiposity on the relationship between age at menarche and blood pressure. This was a nationally representative survey conducted in Brazil in 2013 (Brazilian Health Survey). The participants included 33, 715 women between 18 and 100 years old. Age at menarche was self-reported and outcomes (body mass index [BMI], waist circumference, and blood pressure) were objectively measured. As covariates, data on chronological age, race, educational status, tobacco smoking, leisure physical activity, TV viewing, sodium consumption, alcohol drinking, menopause status, and antihypertensive medication use were obtained by questionnaires. Negative and linear relationships were observed between age at menarche and adiposity indicators. Early maturers presented a greater prevalence of obesity (waist circumference: 56.3% [54.0–58.7] vs. 52.4% [51.4–53.5], BMI: 32.4% [30.2–34.6] vs. 25.1% [24.2–26.0]) than on time/late maturers. Age at menarche was significantly inversely related to blood pressure and adiposity in adulthood (p < 0.05), although these associations were weaker than the association between obesity and early menarche. Adiposity indicators mediated the relationship between age at menarche, and systolic (partly) and diastolic (fully) blood pressure. In conclusion, early maturation is related to obesity and higher blood pressure in adulthood. Obesity is an important mediator of the influence of early maturation on high blood pressure in women.